Fungsi Invers F(x) = x+3 G(x) = -4x H(x) = 5x + 1 ((f^-1 o g^-1) o h^-1 (x))

Fungsi Invers

F(x) = x+3
G(x) = -4x
H(x) = 5x + 1

((f^-1 o g^-1) o h^-1 (x))

Jawaban : -1/20 x – 59/20

Penyelesaian :
f(x) = x+3
y = x+3
x = y-3
f-¹(x) = x-3

g(x) = -4x
y = -4x
x = -¼y
g-¹(x) = -¼x

h(x) = 5x + 1
y = 5x + 1
5x = y-1
x = ⅕(y-1)
h-¹(x) = ⅕(x-1)

(f-¹ o g-¹) o h-¹) (x) = (-¼x-3)o(⅕(x-1))
= -¼(⅕(x-1))-3
= -1/20 x +1/20 – 60/20
= -1/20 x – 59/20

Kesimpulan, (f-¹ o g-¹) o h-¹) (x) = -1/20 x – 59/20

Semoga membantu ya

Baca Juga :  Apa yg dimaksud dg perairan